Um propagandista da República : política, letras e família na trajetória de Joaquim Francisco de Assis Brasil : década de 1880 - Saccol, Tassiana Maria Parcianello (2013)
This paper analyzes the period of republican propaganda in Brazil (between 1880 and 1889) through the agency of a main character: Joaquim Francisco de Assis Brasil. The analysis of the trajectory of this young propagandist and his investments in the world of literacy and politics helps to reflect on two phenomena discussed throughout the text: the circulation of ideas in Brazil in the late nineteenth century and the strength of the republican movement in the countryside and missions in the state Rio Grande do Sul, Southern Brazil. Our focus is on the range of social relations in which Assis Brasil was involved. Therefore, he was always taken in interaction with other individuals such as their family, friends and political associates. The use of prosopography and the concepts of social networking, family and mediation strategy are some of the methodological theoretical contributions that allowed us to perform this research, based on the study of the social context in that period. Thus, it is possible to identify that young propagandists were not used to acting alone but they were part of a project shared by other family members which sought the access to power. Similarly, the existence of some bonds of friendship and kinship as well as the subsequent formulation of the relationship networks among propagandists from the most diverse Brazilian provinces collaborated to spread the republican ideal. On the other hand, by trying to identify the profile of the republicans from the third constituency, who also contributed to the election of Assis Brasil to the position of provincial deputy, we conclude that this group was formed from social rural roots - most of them involved with the raising of cattle, and with strongly hierarchical ideas while the analysis of the profile of the leaders from Rio-Grandense Republican Party demonstrated strong professional feature in this group, even though they belonged to families of rural society elites, who were traditionally involved in conservative politics of the province. At last, our focus is on the performance of Assis Brasil as provincial deputy and about his trial seeking grants and support to the industry of cattle production from the parliament so that it could benefit not only his family but also relatives, friends and his political base in the border region of southern Brazil.